Numerical Calculation of Doppler Steering Laws in Bi- And Multistatic SAR - Mittermayer, Josef; Krieger, Gerhard; Wollstadt, Steffen (IEEE Transactions on Geoscience and Remote Sensing, 2022)
This article defines Doppler steering laws for different bi- and multistatic acquisition geometries for synthetic aperture radar (SAR). Central swath line (CSL) and transmit swath line (TSL) acquisition geometries are introduced. Bistatic zero Doppler steering (BZDS) is defined. Multistatic acquisitions are classified into dedicated and supplementary types. Numerical approaches for the calculation of yaw, pitch, and roll angles are described providing zero Doppler, constant Doppler, and/or full Tx-Rx beam footprint overlap. The appendix provides an approximated analytical approach to calculate yaw and pitch angles to achieve a desired swath line.
Created from Fastlane, Scopus look-up
Keywords: Multistatic satellite attitude steering; synthetic aperture radar (SAR); zero/constant Doppler centroid